Can Tracking Raise the Test Scores of High-Ability Minority Students? - Card, David; Giuliano, Laura (American Economic Review, 2016)
We evaluate a tracking program in a large urban district where schools with at least one gifted fourth grader create a separate “gifted/high achiever” classroom. Most seats are filled by non-gifted high achievers, ranked by previous-year test scores. We study the program's effects on the high achievers using (i) a rank-based regres sion discontinuity design, and (ii) a between-school/cohort analysis. We find significant effects that are concentrated among black and Hispanic participants. Minorities gain 0.5 standard deviation units in fourth-grade reading and math scores, with persistent gains through sixth grade. We find no evidence of negative or positive spillovers on nonparticipants. (JEL I21, J21, J24)